KEGANASAN: TELA’AH TERHADAP KONSEP JIHAD FI SABILILLAH - Rajab, Khairunnas; Mahmud, Fikri (Jurnal Syariah, 2010)
In al-Qur’an, the term jihad does not always mean a battle using a weapon, but can mean a fight in general. For the term of battle using a weapon, al-Qur’an uses “al-Qital” or “al-Harb”. The terms of terrorism and jihad are very different in their application. In Islamic literature, the term terrorism is not found. The term found is al-Hirabah. Al-Hirabah is a crime action committed by people or a group of people armed to terrorize, to kill or to do bloodshed, to seize, to damage properties, plants, animals and so forth. The doer is called al-Muharibun and Qutta’ al-Tariq.